Living with Art - Getlein, Mark (McGraw-Hill, 2008)
Throughout the previous seven editions, this text has earned a reputation for elegance and the highest standards of quality. Living with Art helps students develop an appreciation of art by offering a clear and comprehensive introduction to the visual arts from several perspectives: themes and purposes of art; the vocabulary of art; individual art media (painting, drawing, camera arts, sculpture, architecture, etc.); and the history of art. The book is rich with illustrations drawn from a wide range of artistic cultures and time periods.